Analisis program latihan sepak bola Sekolah Sepak Bola Sekundang di Kabupaten Bengkulu Kepahiang - Doni Saputra (Journal Of Dehasen Educational Review, 2020)
This study aims to determine the implementation of the SSB Sekundang soccer training program, South Bengkulu Regency. The approach method used in this research is qualitative. The research was conducted to determine how the implementation of the SSB Sekundang training program in South Bengkulu Regency made by the trainer whether it has been programmed properly or not and whether it is sustainable.Therefore this research is categorized into the qualitative research category. The population in this study was the athletes of SSB Sekundang of South Bengkulu. The data collection techniques in this study used observation, interview and documentation methods. For a sample of 23 athletes and 2 trainers. The data analysis technique used interactive analysis and domain analysis. From the results of data analysis, qualitative, research results testing, and discussion, it can be concluded that the implementation of the training program has been going well and the following items have been made by the trainer.